ANALISIS FAKTOR INTERNAL PENENTU KEPUASAN PASIEN PUSKESMAS KOTA BANJARMASIN - Achmad Rizal; Agus Jalpi (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2018)
With increasing social circumstances made the patients more and aware of the quality of health services, so that the required quality of service quality improvement better health-oriented patient satisfaction from the results of preliminary observations each patient was found to rate Clinics are expected to create and provide health services to the maximum. However, in general the Clinics currently in accordance with its functions, namely providing a quality service on his patients, reflected on the last two years of patient visits declined by as much as 25% and there are complaints of patients who feel not satisfied against the health service provided at clinics of the city of Banjarmasin in 5 of the 7 patients expressed less satisfied against the Clinics. The purpose of this research is to know the internal factors determining satisfaction patients clinics of the city of Banjarmasin, this type of research with Cross Sectional. The number of respondents who examined 95 respondents. The results of the data collection to be analyzed with the use of univariate statistics, the chi square test bivariat use with the aid of computerized Value significance (a) 0.05. Patient satisfaction in Banjarmasin City Clinics can note that stating satisfied as much as 62%. Variables that have the relationship significantly with patient satisfaction is age, occupation and place of residence of the patient. While the variables that have no relationship significantly with patient satisfaction is the gender and education. Based on the research results, analysis and conclusions there are a couple of suggestions that need to be done to improve the satisfaction of patients against the health service at the health center of the city of Banjarmasin, among others, for the program in improving patient satisfaction Clinics health workers to make it more responsive and always give more attention against a visiting patients to health services especially in the elderly seniors so they always feel taken care of and for more research further expected to unearth the factors causing the old age of the respondents was not satisfied against the health service. Keywords: Health services , Satisfaction patients , the internal factor.